Tongue base reduction with temperature-controlled radiofrequency volumetric tissue reduction for treatment of obstructive sleep apnea Syndrome - Stuck, Boris; Maurer, Joachim T.; Verse, Thomas; Hörmann, Karl (Acta oto-laryngologica, 2002)
In recent years a considerable effort has been made to establish the use of different surgical techniques for the treatment of obstructive sleep apnea syndrome (OSAS). Nevertheless, treatment of hypopharyngeal obstruction due to tongue base hypertrophy remains in many ways an unsolved problem. The aim of this study was to evaluate the safety and efficacy of tongue base reduction with temperature-controlled radiofrequency volumetric tissue reduction in the treatment of OSAS. Twenty patients with OSAS and tongue base hypertrophy were treated with radiofrequency tissue ablation. An intensified treatment protocol was used, delivering 2,800 J per treatment session under local anesthesia. Two nights of polysomnography testing were performed before and after treatment. Daytime sleepiness, snoring and postoperative morbidity were assessed using questionnaires. Mean respiratory disturbance index (RDI) was reduced from 32.1 to 24.9/h after a mean of 3.4 treatment sessions. Six patients (33%) were cured after the procedure (reduction in RDI of S 50% and a postoperative RDI of <15/h) and ten (55%) showed an improvement of >20% in their RDI. Daytime sleepiness and snoring improved significantly. Peri- and postoperative morbidity was low; one severe complication occurred (tongue base abscess). We were able to achieve similar cure and responder rates to those reported in a recently published pilot study but with a reduced number of treatment sessions. We believe that this technique may improve patient acceptance and have beneficial cost implications.
Elektronische Reproduktion der Druckausgabe
Gesehen am 06.05.2022